Orbital plasma welding of small bore tubes - Tazedakis, A. S. (Cranfield University, 1997)
This work was primarily motivated by the industrial need for control of problems associated with the Gas Tungsten Arc Welding (GTAW) of small bore titanium and austenitic stainless steel tubes. These include: pore creation and entrapment in the weld zone, and variability of the fusion zone geometry. The primary aim of this study was the development of a low current orbital plasma welding capability using a structured approach which could lead to defect minimisation. The methodology should also have the potential to be used in a number of different conditions, extending the use of plasma welding in both melt-in and keyhole modes for the orbital welding of small bore tubes. The project originally involved the modification of a totally enclosed orbital GTAW welding head for low current welding operations. It was established that for the current range required for small bore and small to medium thickness tubes, the use of a solid copper torch was sufficient to provide the required heat absorption. A stable arc was produced even for very low current values (down to 7A) while arc voltages were within the operating range of a standard GTA welding power source. Procedural (i.e. off line) control was adopted for identification and optimisation of welding parameters. Since no procedure was available for the proposed welds it was necessary to generate the parameters required for the production of consistent weld profiles. Simultaneously, an expert system has been developed for the determination of optimum process parameters based on empirical models, developed using statistical techniques. Parameter combinations were selected based on physical as well as statistical relevance, providing a measure of confidence when predicting the required weld bead output characteristics. The approach also indicates the influence of the major input parameters on weld bead geometry and defect formation, such as undercut. Two quality acceptance criteria were employed during this investigation, weld bead dimensional accuracy, and the type and seriousness of defects present (penetration / burn-through, porosity and undercut). Off line programming was utilised to control heat build up and to ensure welds were obtained with the desired geometry and minimal defect levels. The end result was the development of a prototype system for low current orbital plasma welding (in both melt-in and keyhole mode) of small bore tubes in a totally enclosed head. Tolerant procedures for low current orbital melt-in and particularly keyhole welding have been generated and a systematic methodology for the prediction and optimisation of welding procedures based on predetermined criteria has been developed.